Economic Valuation of Water in the Alto Chicamocha Irrigation District, Boyacá, Colombia (2023)
The economic valuation of natural resources allows the determination of the monetary value of a public resource without a defined market. Contingent valuation methodology is the most widely used method in the world for assessing the economic value of water. In this study, the estimation of the economic value of irrigation water and payment for a water resource conservation plan of the Alto Chicamocha (Boyacá) Irrigation District was carried out, using the methodological scheme of contingent valuation and the application of surveys for the identification of the perception of social, productive, environmental and economic aspects of the users. The willingness to pay values was calculated with the econometric estimation using probit models in the Stata 16 software. The results indicate a total economic value of 421,998,831.5 COP, a willingness to pay (DAP) of 181 COP per cubic meter of irrigation water, and 10,782.33 COP for a water conservation plan within the territory. The very low statistically ​​determined values show the low perception of the importance of the water resource, both for its conservation and its productive value, on the part of the users. Therefore, it is necessary to develop strategies that take into account the importance of water resources as part of the regional production chain, as well as other research on the valuation of natural resources in order to formulate strategies for efficient use, governance and conservation.